An Exploratory Study of the Effects of the COVID-19 Pandemic and Lockdown on the Emotional and Social Well-being of Students Enrolled at a University of Technology (Journal of Student Affairs in Africa, 2022)
This qualitative descriptive study explored the effects of the COVID-19 pandemic and thesubsequent lockdown on the emotional and social well-being of students enrolled at the DurbanUniversity of Technology, South Africa. A sample of students was selected across all levels of study(first, second and third years and postgraduates), using convenience sampling. Data saturation wasreached after interviewing the fifteenth participant on Microsoft Teams. The interview scheduleincluded details on understanding how the pandemic and the ensuing lockdown affected students’emotional and social well-being. Interviews were recorded, transcribed and subjected to contentand thematic analyses. Four broad themes emerged, viz., fears associated with coronavirus and itstransmission; the lockdown experience; personal anxiety and mental health; as well as financialdistress. Our study highlights the potential risks associated with the emotional and mental healthstatus of our cohort in the advent of the COVID-19 lockdowns that characterised the immediateresponses of the South African Government and institutions of higher learning to the pandemicoutbreak. These data may assist our understanding of the possible adverse effects on emotional andsocial well-being amongst a university population. These are important factors for higher educationinstitutions to consider in order to provide better mental health support to students.